2015
DOI: 10.1055/s-0035-1558115
|View full text |Cite|
|
Sign up to set email alerts
|

A Simple and Sensitive LC-MS/MS Method for Determination of Four Major Active Diterpenoids from Andrographis paniculata in Human Plasma and Its Application to a Pilot Study

Abstract: Andrographis paniculata contains four major active diterpenoids, including andrographolide (1), 14-deoxy-11, 12-didehydroandrographolide (2), neoandrographolide (3), and 14-deoxyandrographolide (4), which exhibit differences in types and/or degrees of their pharmacological activity. Previous pharmacokinetic studies in humans reported only the parameters of compound 1 and its analytical method in human plasma. The purpose of this study was to develop a simple, sensitive, and selective liquid chromatography tand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Furthermore, in consideration of A. paniculata for the treatment of diseases, the key component is compound 1, which is the major diterpenoid found in the highest amount in the plant. Our previous pharmacokinetic study of major active diterpenoids after multiple oral doses of A. paniculata in healthy subjects, with a dose-normalized basis, showed that the amount of 2 that could reach blood circulation was approximately 14 times higher than that of 1 [23,24]. Furthermore, our previous in vitro and in vivo studies showed that the effects of A. paniculata and its major bioactive diterpenoids give some reasons for concern.…”
Section: Clinical Parameters Following Multiple Oral Dose Administrat...mentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, in consideration of A. paniculata for the treatment of diseases, the key component is compound 1, which is the major diterpenoid found in the highest amount in the plant. Our previous pharmacokinetic study of major active diterpenoids after multiple oral doses of A. paniculata in healthy subjects, with a dose-normalized basis, showed that the amount of 2 that could reach blood circulation was approximately 14 times higher than that of 1 [23,24]. Furthermore, our previous in vitro and in vivo studies showed that the effects of A. paniculata and its major bioactive diterpenoids give some reasons for concern.…”
Section: Clinical Parameters Following Multiple Oral Dose Administrat...mentioning
confidence: 98%
“…The simultaneous determination of major active diterpenoids of A. paniculata in human plasma was employed using a validated LC-MS/MS technique [23]. Briefly, 50.0 ng/mL of cortisone (internal standard) and 800 µL of methanol were added to a 200-µL aliquot of plasma samples.…”
Section: Determination Of Plasma Concentrations Of Andrographolide An...mentioning
confidence: 99%
“…While the clinical benefits of the extract (60 mg of andrographolide/dose) have been evaluated, the data on the pharmacokinetics of this dose remain limited. Therefore, one of the objectives of this study was to investigate the clinical pharmacokinetics of andrographolide (AP1), a major phytoconstituent of this plant, and of other diterpenoid derivatives 6 – 8 including: 14-deoxy-11, 12-didehydroandrographolide (AP3), neoandrographolide (AP4), and 14-deoxyandrographolide (AP6) after a single oral administration of A. paniculata extract (equivalent to 60 mg/dose of andrographolide).…”
Section: Introductionmentioning
confidence: 99%
“…The value is lower than the IC 50 value of 6.18 µM obtained in this study. Another two pharmacokinetic studies of andrographolide showed that its maximum concentration in plasma were 58.6 ng/mL (0.17 µM) and 32.41 ng/mL (0.09 µM) after ingestion of 200 mg and 32.64 mg of andrographolide for three times a day, respectively [ 59 , 60 ]. As the andrographolide concentration in plasma reportedly ranged from 0.09 to 3.8 µM which is less than the obtained IC 50 value in HLM (6.18 ± 1.27 µM), inhibition of hepatic systemic clearance of UGT2B7 substrates in humans seems implausible.…”
Section: Discussionmentioning
confidence: 99%